PHARMACOGNOSTIC PARAMETERS OF SALVADORA OLEOIDES DECNE. LEAVES - Singh, Sumitra; Sharma, Surendra Kr; Naresh, Vijay (Asian Journal of Pharmaceutical Research and Development, 2013)
Salvadora oleoides Decne (Salvadoraceae) is locally known as ‘Jaal’ to have many uses in ethnomedicine. Establishment of pharmacognostic profile of the leaves will assist in standardization and identification of samples. The present study deals with pharmacognostic examination of macroscopical and microscopical characters of leaves of Salvadora oleoides Decne including leaf constant, ash values, extractive values, fluorescence analysis and phytochemical screening of the extracts.